Model Pemberdayaan Masyarakat Perspektif Islam - Susilo, Adib (FALAH Jurnal Ekonomi Syariah, 2016)
Welfare become the trending topic of the economy from the country. One of the reasons why the country exist is to ensure welfare, just and equality for its citizens. To achieve welfare, required a symbiotic mutalisme between the government as a society and the state. Hence, direct assistance shaped material from the government to public is not a solution. Thus community empowerment is required. Islam as komperhensif teaching which implemented community empowerment since the first time. Where the messenger united between supporters and emigrants and empower them in order to achieve prosperity. The type of this research is library research with the normative descriptive methods. The result shows that the people in community empowerment evenly distributed in some principle which has been implemented by the messenger in an effort to daâwah Islamiyyah. Those principle are: justice, equality, participation, award, and helping others (taâawun). The model of empowerment, used approach parsial-kontinu and a structural approach so as to achieve three dimensions the Muslim community, which is: faith dimensions, science dimensions and the social dimension.